2019
DOI: 10.3390/ma12244223
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution and Mechanical Properties of AZ80 Mg Alloy during Annular Channel Angular Extrusion Process and Heat Treatment

Abstract: Microstructure evolution and mechanical properties of AZ80 Mg alloy during annular channel angular extrusion (350 °C) and heat treatment with varying parameters were investigated, respectively. The results showed that dynamic recrystallization of Mg grains was developed and the dendritic eutectic β-Mg17Al12 phases formed during the solidification were broken into small β-phase particles after hot extrusion. Moreover, a weak texture with two dominant peaks formed owing to the significant grain refinement and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The misorientation of these substructures was gradually increased as the number of thermal cycles increasing until equiaxed grains were formed. Furthermore, the average grain sizes in samples annealed at 150 • C, 350 • C and 400 • C after thermal cycling were reduced from 120.2 µm to 36.3 µm, from 82.4 µm to 28.5 µm and from 58.7 µm to 35.4 µm, respectively, indicating that the increase of the number of equiaxed grains contributed to the decrease of the average grain size and that there was a limit value of about 30 µm in the grain size after the thermal cycling of ∆T = 120 • C. The change of defects and the change of the orientation of grains that contributed to the dimensional instability may be caused by the formation of the equiaxed grains [15,19]. Thus, the formation of equiaxed grains may be the key factor in the dimensional instability of materials during thermal cycling.…”
Section: Ebsd Analysis Of Microstructure After Thermal Cyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…The misorientation of these substructures was gradually increased as the number of thermal cycles increasing until equiaxed grains were formed. Furthermore, the average grain sizes in samples annealed at 150 • C, 350 • C and 400 • C after thermal cycling were reduced from 120.2 µm to 36.3 µm, from 82.4 µm to 28.5 µm and from 58.7 µm to 35.4 µm, respectively, indicating that the increase of the number of equiaxed grains contributed to the decrease of the average grain size and that there was a limit value of about 30 µm in the grain size after the thermal cycling of ∆T = 120 • C. The change of defects and the change of the orientation of grains that contributed to the dimensional instability may be caused by the formation of the equiaxed grains [15,19]. Thus, the formation of equiaxed grains may be the key factor in the dimensional instability of materials during thermal cycling.…”
Section: Ebsd Analysis Of Microstructure After Thermal Cyclingmentioning
confidence: 99%
“…The residual plastic strain along the axial direction of the extruded LY12 Al alloy after thermal cycling was about 13 times than that along the transverse direction [15]. The rolled alloy sheet investigated by several scholars demonstrates significant anisotropy in micro-yield, creep deformation and tensile properties due to the strong texture [16][17][18][19]. The strength degradation of commercially pure Al after annealing was the result of the evolution of texture and sub-grain growth during the recovery and recrystallization, which depended on the annealing temperature [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there was a slight tendency towards smaller grain sizes in materials with 10 wt.% of Al 2 O 3 particles. It was also reported [25][26][27][28] that the hot deformation process of such materials leads to the creation of coherent Mg 17 Al 12 intermetallic precipitates.…”
Section: Introductionmentioning
confidence: 90%
“…Many previous studies have shown that the precipitation of the second phase is one of the important factors affecting the dimensional stability of materials [ 24 , 25 , 26 , 27 , 28 , 29 ]. Song et al believed that when an external force is applied to the Al–Cu–Mg alloy during aging, the precipitated phase S’ in 2024 aluminum alloy will be uniformly distributed with the increase in the external stress, increasing the micro yield strength of the material, thereby improving the dimensional stability of 2024 aluminum alloy, which is related to the pinning effect of S’ relative dislocation [ 30 ].…”
Section: Introductionmentioning
confidence: 99%